Sosialisasi SOP dan K3 Penggunaan Mesin Sealer Untuk Meningkatkan Keselamatan Kerja pada UMKM - Shintya Dewi, Marysca; Komarudin; Desi Ramayanti (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
Cogreg Village in Parung District, Bogor Regency, has great potential in the micro, small and medium enterprise (MSME) sector, especially through the Kemuning Mandiri UKM which operates in the field of processed catfish and snacks. However, these SMEs face various challenges such as inadequate product packaging, limited marketing, and low awareness and knowledge about work safety (K3). These problems hinder competitiveness and business growth. This research aims to implement solutions in the form of socialization, training and application of sealer technology to improve product quality, work safety and production efficiency. Through the stages of socialization, training, technology application, mentoring, and program sustainability, the results achieved show a significant increase in technical knowledge and K3 practices, optimization of product packaging, and expansion of business networks. Before the intervention, products were packaged manually with low shelf life and limited marketing. After training, products have better, consistent and safer packaging quality, and there is an increase in partners' understanding of the importance of SOP and K3. This program not only increases product competitiveness but also contributes to strengthening the local economy. Thus, this research makes a real contribution in increasing the capacity and quality of Kemuning Mandiri UKM products in a sustainable manner